Portal Website Analysis Using ISO / IEC 9126-4 Metric Effectiveness (Case Study Indonesia Wi-Fi Portal Website) - Refky Jumrotuhuda (International Conference on Engineering and Technology Development (ICETD), 2014)
According to the increasing of human necessity, Development of technology have to bring the same increasing in order to support and facilitate every activity in all sorts of the human life. Internet is the one of the real outcome from the development of technology. Indonesia Wi-Fi is a public internet network server based on Wi-Fi/Hotspot technology developed by TELKOM Group and other related operator to the TELKOM enterprise. Portal website of Indonesia Wi-Fi is used as a portal for user to connect the internet network. In order to develop this portal website for the better service, a correct and pledge information. The quality in use of this portal website have to be evaluated. One of the standards can be used to evaluate this portal website is ISO/IEC 9126-4 Effectiveness metrics. ISO/IEC 9126-4 Effectiveness metrics is an international standard published by ISO (International Organisation for Standardisation) and IEC (International Electro-technical Commission) to measure the quality in use of software in effectiveness aspect. In this research, portal website of Indonesia Wi-Fi measured using ISO/IEC 9126-4 Effectiveness metrics. The measurement result show score 1 in Task Effectiveness metric, score 1 in Task Completion metric and score 1 in Error Frequency metric. The results prove that portal website of Indonesia Wi-Fi is good quality using ISO/IEC 9126-4 Effectiveness metrics measurement.